Treatment of Severe Anterior Open-bite Accompany with Impacted Canine:A Case Report - Fataneh Ghorbanyjavadpour (Isfahan University of Medical Sciences, 2022)
The anterior open bite is a multifactorial malocclusion and a challenge between orthodontists. Based on the origin, divided in two types as dental and skeletal, and appear in the anterior or posterior segments, (unilateral or bilateral). Dental open-bite in the most of patients have environmental etiologic factor such as oral habits, tongue trust, mouth breathing, large tongue. In skeletal type, excessive vertical growth of the maxilla is etiologic factor and accompany with downward-backward rotation of the mandible.Case Report:The case was a 27years woman with an anterior open bite and unilateral impacted upper canine and congenital missing of lower 2ndpremolar in the left side and retained 2ndlower deciduous molar and upper canine in the left side. She consulted for orthodontic treatment in Tehran Dental School of Shahid Beheshti University of Medical Sciences in October of 2017.The Orthodontic treatment was down with MBT slot 22 system (USA. Orthoorganizer, inc) for apply extrusive force on impacted upper canine in left side with auxiliary 014 ss, segmented arch wire. loop arch wire technique with 16×22 ss rectangular continuous arch wire was used for space closing in extraction site and correction overbite. The extracted teeth were right lower 2ndpremolar and left 2nddeciduous molar and 1stpremolars in upper arch. As recommended advancement genioplasty for correction chin deficiency the patient refused it. Conclusion:In this technique we used Orthodontic treatment alone instead of Orthognathic surgery for open bite correction